Solid waste collection optimization objectives, constraints, modeling approaches, and their challenges toward achieving sustainable development goals - Hannan M.A.; Hossain Lipu M.S.; Akhtar M.; Begum R.A.; Al Mamun M.A.; Hussain A.; Mia M.S.; Basri H. (Elsevier Ltd, 2023)
Planning; Population statistics; Solid wastes; Sustainable development; Complex Processes; Logistics management; Maintenance cost; Mathematical computation; Optimization approach; Optimization method; Solid waste collection; Waste collection; Constrained optimization